1,3-Bis{[(2,6-dimethylphenyl)sulfanyl]methyl}benzene - Garita Salazar, Bruno (2019)
The structure of the title compound, C24H26S2, an example of a pincer ligand with an SCS-chelation motif, illustrates the steric effects of the methyl groups in the thiophenyl rings at the 2- and 6-positions, forcing a dissimilar spatial orientation of the thiophenyl rings relative to the central aryl group [dihedral angles = 33.58 (7) and 40.49 (7)°]. In the crystal, weak S⋯S contacts [3.4009 (7) Å] link the molecules into inversion dimers.